Seasonal-to-Multiyear Large Ensemble (SMYLE) Experiment ... - Yeager, Stephen (UCAR/NCAR - CISL - CDP, 2022)
The SMYLE set of initialized hindcasts using CESM2 that is specifically designed to explore Earth system predictability at forecast lead times ranging from 1 month out to 2 years. In addition to extensive hindcast output from all CESM2 component models, SMYLE includes historical reconstructions for the ocean, sea ice, and land component models; an experimental setup that can be replicated and/or modified; and python code for performing post-processing and skill assessment. Details are provided below: SMYLE at a glance CESM2 model: ocean (POP2, 1°, 60L); atmosphere (CAM6-FV, 1°, 32L); land (CLM5); sea ice (CICE5); ocean biogeochemistry (MARBL) Hindcasts initialized quarterly (1st of February, May, August, November) from 1970 to 2019 24-month simulations 20-member ensembles CAM6 initialization: JRA55 Reanalysis POP2 initialization: JRA55-do forced ocean/sea-ice (FOSI) simulation CICE5 initialization: JRA55-do forced ocean/sea-ice (FOSI) simulation CLM5 initialization: CRU-JRAv2 forced land simulation ...